The effects of electron donors on the growth of sulfate-reducing bacteria in copper-zinc and gold mine tailings from Timmins, Ontario - Roy, Michael (University of Ottawa (Canada), 2004)
Previous studies have shown that sulfate-reducing bacteria (SRB) are present and possibly active in gold and copper-zinc mine tailings. Sulfate-reducing bacteria can play an important role in the geochemistry of the mine tailings as they are responsible for the precipitation of diagenetic iron monosulfides and pyrite, a potential source for the generation of acid mine drainage. On the other hand, the formation of iron monosulfides can also serve to immobilize trace metals, and therefore has potential benefits to the tailing water systems. In addition, microbial sulfate reduction generates alkalinity which can be used to neutralize some of the acidity generated by the oxidation of metal sulfides. To better understand the role that sulfate-reducing bacteria play on the geochemistry of mine tailings, this present study was designed to identify some of the factors controlling the growth of sulfate-reducing bacteria in the tailings. The main goal was to determine the influence of organic electron donors (specifically lactate, acetate, formate and pyruvate) on microbial sulfate reduction in closed batch systems possessing physico-chemical conditions (pH, redox potential) matching the in situ conditions of the tailings in order to identify the preferred electron donor. (Abstract shortened by UMI.)
Keywords: Geology.